Identifikasi Escherichia Coli Pada Es Batu Yang Dijual Di Warung Makan Kelurahan Liliba Kupang - I Gede Putu Arnawa; Ni Made Susilawati; Marselina Sanbein (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Ice cubes are a food product that is often consumed by the community. Ice cubes are usually mixed in drinks to add freshness. Ice cubes are made from drinking water frozen at 0°C, although low temperatures can inhibit the growth of microorganism cells, ice cubes still have the possibility of containing contaminant microorganisms. Ice cubes that can cause diarrhea are ice cubes that contain pathogenic bacteria, one of which is Escherichia coli. Therefore it is necessary to check the quality of ice cubes microbiologically. This study aims to detect the presence of Escherichia coli in ice cubes sold by food stalls in the Liliba Village, Kupang. This type of research uses a descriptive method, where the population in this study is ice cubes which are sold in 10 different stalls in Liliba Kupang Village. The method used is Most Probable Number (MPN) with a variance of 5-1-1 followed by Gram staining and IMVIC test. From the results of the study, it can be found that ice cubes are sold in food stalls in Liliba Kupang Village, from 10 samples of ice cubes there is 1 sample that contains 10% Escherichia coli bacteria.